Acute Kidney Injury is Aggravated in Aged Mice by the Exacerbation of Proinflammatory Processes - Marquez-Exposito, Laura; Tejedor-Santamaria, Lucia; Santos-Sanchez, Laura; Valentijn, Floris A.; Cantero-Navarro, Elena; Rayego-Mateos, Sandra; Rodrigues-Diez, Raul R.; Tejera-Muñoz, Antonio; Marchant, Vanessa; Sanz, Ana B.; Ortiz, Alberto; Goldschmeding, Roel; et al. (Frontiers in Pharmacology, 2021)
Acute kidney injury (AKI) is more frequent in elderly patients. Mechanisms contributing to AKI (tubular cell death, inflammatory cell infiltration, impaired mitochondrial function, and prolonged cell-cycle arrest) have been linked to cellular senescence, a process implicated in regeneration failure and progression to fibrosis. However, the molecular and pathological basis of the age-related increase in AKI incidence is not completely understood. To explore these mechanisms, experimental AKI was induced by folic acid (FA) administration in young (3-months-old) and old (1-year-old) mice, and kidneys were evaluated in the early phase of AKI, at 48 hours. Tubular damage score, KIM-1 expression, the recruitment of infiltrating immune cells (mainly neutrophils and macrophages) and proinflammatory gene expression were higher in AKI kidneys of old than of young mice. Tubular cell death in FA-AKI involves several pathways, such as regulated necrosis and apoptosis. Ferroptosis and necroptosis cell-death pathways were upregulated in old AKI kidneys. In contrast, caspase 3 activation was only found in young but not in old mice. Moreover, the antiapoptotic factor BCL-xL was significantly overexpressed in old injured kidneys, showing an age-related apoptosis suppression. AKI kidneys displayed evidence of cellular senescence, such as increased levels of cyclin dependent kinase inhibitors p16ink4a and p21cip1, and of the DNA damage response marker γH2AX. Furthermore, p21cip1 mRNA expression and nuclear staining for p21cip1 and γH2AX were higher in old than in young FA-AKI mice, as well as the expression of senescence-associated secretory phenotype components (Il-6, Tgfb1, Ctgf and Serpine1). Interestingly, some infiltrating immune cells were p21 or γH2AX positive, suggesting that molecular senescence in the immune cells (“immunosenescence”) are involved in the increased severity of AKI in old mice. In contrast, expression of renal protective factors was dramatically downregulated in old AKI mice, including that antiaging factor Klotho and the mitochondrial biogenesis driver PGC-1α. In conclusion, aging resulted in more severe AKI after the exposure to toxic compounds. This increased toxicity may be related to magnification of proinflammatory-related pathways in older mice, including a switch to a proinflammatory cell death (necroptosis) instead of apoptosis, and overactivation of cellular senescence of resident renal cells and infiltrating inflammatory cells.